2018
DOI: 10.1080/15298868.2018.1558107
|View full text |Cite
|
Sign up to set email alerts
|

Finding meaning in self-control: The effect of self-control on the perception of meaning in life

Abstract: The present research explored whether self-control is associated with the perception of meaning in life. A week-long daily diary study (Study 1) showed trait self-control (but not daily experiences of self-control failure) to be positively associated with a general sense of meaning in life and daily experiences of meaning. This association was robust against controlling for life satisfaction, positive and negative affect. Study 2 tested two potential mechanisms underlying the association between trait self-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 54 publications
1
32
0
5
Order By: Relevance
“…The study was conducted online from June 8 to 16, 2020. After an explanation of what goals are ( Stavrova et al, 2019 ; Stavrova et al, 2020 ), participants were asked to write down one personal goal that they had started pursuing before the lockdown and that they still wanted to achieve. Then, they wrote down up to five behaviors they had been using to achieve this goal before the lockdown started.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted online from June 8 to 16, 2020. After an explanation of what goals are ( Stavrova et al, 2019 ; Stavrova et al, 2020 ), participants were asked to write down one personal goal that they had started pursuing before the lockdown and that they still wanted to achieve. Then, they wrote down up to five behaviors they had been using to achieve this goal before the lockdown started.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research on self-control has shown that one of the reasons why people with higher (vs. lower) self-control are more successful at goal attainment is because they use adaptive behavioral strategies, such as turning goal-directed behaviors into habits ( Adriaanse, Kroese, Gillebaart, & De Ridder, 2014 ; De Ridder & Gillebaart, 2017 ; Ent, Baumeister, & Tice, 2015 ; Galla & Duckworth, 2015 ; Stavrova, Pronk, & Kokkoris, 2020 ; Stavrova, Pronk, & Kokkoris, 2019 ). This tendency to develop “beneficial habits” could facilitate goal attainment during self-quarantine for high self-control individuals.…”
Section: Introductionmentioning
confidence: 99%
“…negatively associated with search for meaning in life (Li et al, 2019). Given that having a sense of structure in life has been found to mediate the positive association between presence of meaning in life and selfcontrol (Stavrova et al, 2018), it may be that when a person acquires or enters into adult roles that provide meaning in life this leads to a structured lifestyle (e.g. having children or stable employment and an early waking routine).…”
Section: Variablementioning
confidence: 99%
“…Self-control is positively associated with presence of meaning in life and negatively associated with search for meaning in life (Li, Salcuni, & Delvecchio, 2019). One study demonstrated that the positive association between self-control and meaning in life was mediated by the perception of having structure in life (Stavrova, Pronk, & Kokkoris, 2018). Therefore, presence of meaning in life may facilitate and maintain self-control through the ability for a person to organise and structure their life, whereas this is potentially lacking in people who are searching for meaning in life.…”
Section: Introductionmentioning
confidence: 99%
“…Persepsi pada kehidupan seseorang merupakan representasi bermakna sebagai prediktor penting pada hasil kehidupan positif (Stavrova et al, 2020). Sementara itu, Walgito (2003) mendefinisikan persepsi sebagai sebuah proses pengorganisasian dan penginrepretasian terhadap stimulus yang diterima oleh setiap individu sehingga merupakan sesuatu yang berarti dan aktivitas yang integrated dalam diri individu tersebut.…”
Section: Pendahuluanunclassified